 # 6.5 – Applying Systems of Linear Equations

## Presentation on theme: "6.5 – Applying Systems of Linear Equations"— Presentation transcript:

6.5 – Applying Systems of Linear Equations

Ex x + 4y = -25 2x – 3y = 6

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y”

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x”

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x”

Ex [3x + 4y = -25] -3[2x – 3y = 6] Eliminate “x”

Ex [3x + 4y = -25] -3[2x – 3y = 6] Eliminate “x” 6x + 8y = -50 -6x +9y = -18

Ex [3x + 4y = -25] -3[2x – 3y = 6] Eliminate “x” 6x + 8y = -50 -6x +9y = -18

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” 6x + 8y = -50 -6x +9y = -18 17y = -68

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” 6x + 8y = -50 -6x +9y = y = -68

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” 6x + 8y = -50 -6x +9y = y = -68 y = -4

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” 6x + 8y = -50 -6x +9y = -18 17y = -68 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y” 6x + 8y = -50 -6x +9y = -18 17y = -68 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y” 6x + 8y = -50 -6x +9y = -18 17y = -68 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex [3x + 4y = -25] 4[2x – 3y = 6] Eliminate “x” OR Eliminate “y” 6x + 8y = -50 -6x +9y = -18 17y = -68 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex [3x + 4y = -25] 4[2x – 3y = 6] Eliminate “x” OR Eliminate “y” 6x + 8y = x + 12y = -75 -6x +9y = x – 12y = 24 17y = -68 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y” 6x + 8y = x + 12y = -75 -6x +9y = x – 12y = 24 17y = x = -51 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y” 6x + 8y = x + 12y = -75 -6x +9y = x – 12y = 24 17y = x = -51 y = -4 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y” 6x + 8y = x + 12y = -75 -6x +9y = x – 12y = 24 17y = x = -51 y = x = -3 3x + 4y = -25 3x + 4(-4) = -25 3x – 16 = -25 3x = -9 x = -3 (-3, -4)

Ex x + 4y = -25 2x – 3y = 6 Eliminate “x” OR Eliminate “y” 6x + 8y = x + 12y = -75 -6x +9y = x – 12y = 24 17y = x = -51 y = x = -3 3x + 4y = x + 4y = -25 3x + 4(-4) = (-3) + 4y = -25 3x – 16 = y = -25 3x = y = -16 x = y = -4 (-3, -4)

Ex. 2 Determine the best method to solve the system of equations
Ex. 2 Determine the best method to solve the system of equations. Then solve the system. 4x – 3y = 12 x + 2y = 14

Ex. 2 Determine the best method to solve the system of equations
Ex. 2 Determine the best method to solve the system of equations. Then solve the system. 4x – 3y = 12 -4[ x + 2y = 14]

Ex. 2 Determine the best method to solve the system of equations
Ex. 2 Determine the best method to solve the system of equations. Then solve the system. 4x – 3y = 12 -4[ x + 2y = 14] 4x – 3y = 12

Ex. 2 Determine the best method to solve the system of equations
Ex. 2 Determine the best method to solve the system of equations. Then solve the system. 4x – 3y = 12 -4[ x + 2y = 14] 4x – 3y = 12 -4x – 8y = -56

Ex. 2 Determine the best method to solve the system of equations
Ex. 2 Determine the best method to solve the system of equations. Then solve the system. 4x – 3y = 12 -4[ x + 2y = 14] 4x – 3y = x – 3(4) = 12 -4x – 8y = x – 12 = 12 -11y = x = 24 y = x = 6 (6,4)

Ex.3 3x – 7y = -14 5x + 2y = 45

Ex x – 7y = -14 5x + 2y = 45 2[3x – 7y = -14] [3x – 7y = -14] 7[5x + 2y = 45] -3[5x + 2y = 45] 6x – 14y = x – 35y = -70 35x + 14y = x – 6y = -135 41x = y = -205 x = y = 5 3x – 7y = x – 7y = -14 3(7) – 7y = x – 7(5) = -14 21 – 7y = x – 35 = -14 -7y = x = 21 y = (7,5) x = 7